2017
DOI: 10.3847/1538-4357/aa755f
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-automatic Determination of Coronal Mass Ejections’ Kinematics in 3D

Abstract: Coronal mass ejection (CME) events are among the main drivers of geomagnetic disturbances, and hence play a central role in the Sun–Earth system. Their monitoring and, in particular, the determination of their speed and direction of propagation are key issues for the forecasting of space weather near to Earth. We have implemented a method to track CME events in three dimensions by combining triangulation and tie-pointing analysis with a supervised computer vision algorithm. This novel approach does not rely on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…The overall performance of the supervised computer vision algorithm CORSET as well as the direct comparison with measurements from other catalogs have already been addressed and briefly discussed in previous works (see, e.g., Goussies et al 2010;Braga et al 2013Braga et al , 2017. However, the number of events analyzed in these works falls short of meaningful statistics to allow us to draw a general picture of the caveats and benefits of such a technique.…”
Section: Lessons Learned From Applying a Supervised Computer Vision Amentioning
confidence: 99%
“…The overall performance of the supervised computer vision algorithm CORSET as well as the direct comparison with measurements from other catalogs have already been addressed and briefly discussed in previous works (see, e.g., Goussies et al 2010;Braga et al 2013Braga et al , 2017. However, the number of events analyzed in these works falls short of meaningful statistics to allow us to draw a general picture of the caveats and benefits of such a technique.…”
Section: Lessons Learned From Applying a Supervised Computer Vision Amentioning
confidence: 99%
“…Triangulation is yet another methodology to derive the CME kinematics. In this case, co‐temporal observations are needed, e.g., from the twin heliospheric imagers or coronagraphs onboard STEREO (e.g., Braga et al., 2017; Y. Liu et al., 2010, 2011; Liewer et al., 2011). This methodology normally requires selection and tracking of particular point‐like features in each viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al (2015a) provided a method to investigate the CME kinematics via determining the radial mass transport process throughout the entire CME, which is capable of the estimation of the radial flow speed inside the CME. Braga et al (2017) used the CORSET3D to determine the tie-points along the CME front automatically in three-dimensional (3D) space and derived the average two-dimensional (2D) speed of CMEs' fronts in the Stonyhurst coordinate system. Compared with these studies, all of these results have never shown the 2D kinetic and potential energy distributions of CMEs.…”
Section: Introductionmentioning
confidence: 99%